Society - Water - Technology : A Critical Appraisal of Major Water Engineering Projects - Bens, Oliver; Bismuth, Christine; Hüttl, Reinhard F.; Hoechstetter, Sebastian (Cham Springer Nature, 2016)
Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies; Environmental Economics; International Environmental Law
Keywords: Environmental Economics; International Environmental Law; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies